Linseed oil improves hepatic insulin resistance in obese mice through modulating mitochondrial quality control. (February 2019) - Yu, Xiao; Huang, Shasha; Deng, Qianchun; Tang, Yuhan; Yao, Ping; Tang, Hu; Dong, Xuyan
Graphical abstract: Highlights: Linseed oil improved hepatic insulin resistance in obese mice. Linseed oil restored hepatic mitochondrial biogenesis, fusion and mitophagy dynamics. Linseed oil modulated specific location of ALA, DPA and DHA in hepatic mitochondria. Abstract: N-3 polyunsaturated fatty acids, especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), mitigate the progression of obesity-associated insulin resistance. However, the knowledge on the metabolic response and underlying mechanism of α-linolenic acid-rich linseed oil (ALA-LO) on insulin resistance was still limited. The results showed that lard-based high fat diet (HFD) feeding for 16 weeks (60% of total calories from fat) led to imbalanced lipid synthesis-oxidation, defect insulin signaling and serious mitochondrial damage in mice liver, which was attenuated by LO. Moreover, LO blocked chronic HFD-induced mitophagy suppression, and improved mitochondrial biogenesis and fusion process in mice liver. Importantly, the specific location of ALA, and its n-3 derivatives docosapentenoic acid (DPA) and DHA in mitochondrial membrane was observed, concomitant with upregulation of SIRT1, PPARγ coactivator-1α (PGC-1α) and extracellular signal regulated kinase (ERK) in mice liver. LO improves hepatic insulin resistance in obese mice partly by restoring mitochondrial quality control network.